(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2021)
Suicide is a major public health problem and one of the leading causes of deaths worldwide. The effects of suicide go beyond the person who acts to take his/her life; it can have lasting effect on family, friends and communities. The role of a nurse specific to suicide prevention includes both system and patient level interventions. Objectives of the study: · To assess the existing knowledge and attitude regarding care of attempted suicide patients among staff nurses. · To evaluate the effectiveness of self –instructional module regarding care of attempted suicide patients among staff nurses. · To find out the association of post -test knowledge and attitude regarding care of attempted suicide patients among staff nurses with selected demographic variables. Materials and Methods: In this pre- experimental research study non probability convenient sampling technique was used to select 60 staff nurses from selected Hospitals. A self- structured questionnaire and attitude scale was used to assess the knowledge and attitude of the staff nurses regarding the care of attempted suicide patients. Result: The finding of the study revealed that majority 95% (57)of staff nurses had moderate knowledge and only 5% (3) had inadequate knowledge regarding care of attempted suicide patients in pre-test. After going through Self Instructional Module, 83.37 % (50) of the staff nurses had adequate knowledge and 16.66% (10) had moderate knowledge regarding care of attempted suicide patients. The attitude scale findings revealed that 100% (60)of staff nurses had neutral attitude regarding care of attempted suicide patients in pre-test and in post-test 100%(60) had positive attitude regarding care of attempted suicide patients. Conclusion: Study concludes that going through Self-Instructional module helps method in improving knowledge and attitude of the staff nurses regarding care of attempted suicide patients.